ANALISIS KUESIONER ONLINE KESIAPAN MENGAJAR DAN PENGALAMAN MENGAJAR TERHADAP PELATIHAN PEKERTI DAN AA: Teaching Readiness, Teaching Experience, Teaching Training - -, Riswan (JURNAL AKADEMIKA, 2019)
This study aims to find out whether lecturer certification supported by Pekerti and AA training has an impact on teaching readiness and teaching experience. This research uses a case study methodology with the object of study of IS and IT lecturers. The research data were obtained through an online research questionnaire in the WhatsApp STMIK Nurdin Hamzah group in the form of 1. Readiness to teach 19 question items, 2. Experience teaching 17 question items, item values were assessed on a Likert scale. The data was processed using SPSS, the results of data processing showed that the research was responded by 18 lecturers, 13 lecturers of study program SI and 5 lecturers of study program IT. The two groups of questionnaires contained different perceptions of lecturers on questions that should have the same perception. The results of this study are very important for lecturers and academic managers to formulate whether additional pedagogical training is needed for lecturers on the teaching process carried out.